How Life History Characteristics and Environmental Forcing Shape Settlement Success of Coral Reef Fishes - Wong-Ala, Jennifer A. T. K.; Comfort, Christina M.; Gove, Jamison M.; Hixon, Mark A.; McManus, Margaret A.; Powell, Brian S.; Whitney, Jonathan L.; Neuheimer, Anna B. (Frontiers in Marine Science, 2018)
Larval settlement is shaped by the interaction of biological processes (e.g., life history strategies, behavior etc.) and the environment (e.g., temperature, currents etc.). This is particularly true for many reef fishes where larval stages disperse offshore, often spending weeks to months in the pelagic realm before settling to shallow-water reefs. Our ability to predict reef fish settlement and subsequent recruitment and population dynamics depends on our ability to characterize how biological processes interact with the dynamic physical environment. Here we develop and apply an individual-based model that combines biological processes with high-resolution physical forcing to predict larval fish dispersal and settlement over time and space. Our model tracks individual larval fish from spawning to settlement and allows for the inclusion of biologically relevant stochasticity (individual variability) in modeled processes. Our model is also trait-based, which allows individuals to vary in life history characteristics, making it possible to mechanistically link the resulting variability in settlement probabilities to underlying traits such as spawning date and location, pelagic larval duration (PLD), body morphology, etc. We employ our biophysical model to examine how biology interacts with the physical environment to shape settlement predictions for reef fish off western and southern Hawai‘i Island. Linked to prevailing surface currents, we find increased probabilities of settling associated with shorter PLDs and fish spawned in southern and southwestern locations. Superimposed on this, eddies, common to leeward Hawai‘i Island, offer a second pathway to successful settlement for individuals with longer PLDs, particularly for fish spawning in summer months. Finally, we illustrate how lunar-timed spawning as well as morphological features (e.g., fin and head spines) may impact settlement success by altering the mortality landscape experienced by larvae. This work identifies life history characteristics that predict the self-recruitment pathways necessary for population persistence for the relatively isolated Hawai‘i Island. Our results can be used to develop future hypotheses regarding temporal and spatial variation in recruitment for reef fishes on Hawai‘i Island and beyond.